Anterior Segment Complications Following Intravitreal Injection - Mackenbrock, Lars H. B.; Auffarth, Gerd U.; Albrecht, Michael; Naujokaitis, Tadas; Kessler, Lucy J.; Mayer, Christian S.; Khoramnia, Ramin (Klinische Monatsblätter für Augenheilkunde, 2024)
Intravitreal injections (IVI s) have gained increased popularity in the past decades and are used to treat a multitude of ailments. In 2010, the total number of IVI s surpassed the number of cataract surgeries performed, making it the most common procedure in ophthalmology. As the number of injections increases, so does the number of injected-related complications. While complications in the posterior segment, such as retinal detachment or endophthalmitis, are detrimental to visual function and have therefore been well documented, IVI s can also lead to complications in the anterior segment. These include hyphema, inflammation of the sterile anterior segment (incidence rate of 0.05 to 1.1% depending on the drug), implant migration with corneal decompensation (incidence rate of 0.43%), iatrogenic lens damage (incidence rate of 0.07%), accelerated cataract formation (up to 50% for steroids and 10.9% for anti-VEGF), and an increased complication rate during subsequent cataract surgery (up to 4% per IVI). Most of these complications occur immediately and have a good prognosis if treated correctly. However, the increased risk of complications during subsequent surgery demonstrates that IVI s can also have long-term complications, a topic that needs to be explored further in future research projects.
Keywords: intravitreal injection; anti-VEGF; cataract; complication; intraocular inflammation; vitreous